2016
DOI: 10.1002/imhj.21564
|View full text |Cite|
|
Sign up to set email alerts
|

A Web-Based Survey of Mother-Infant Bond, Attachment Experiences, and Metacognition in Posttraumatic Stress Following Childbirth

Abstract: Metacognition may have a key role in postnatal psychological distress. Where postnatal depression or traumatic birth experiences are identified, screening for posttraumatic stress is strongly indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 94 publications
1
15
2
Order By: Relevance
“…Only one other study has investigated the mechanistic relationships of maternal postpartum affective symptoms (depression/anxiety/psychological distress), PTSD-CB, and mother-infant bonding within the first year postpartum. This study found that the relationship between PTSD-CB symptoms and mother-infant bonding was mediated by depressive symptoms ( 26 ). This is in contrast to our findings of a lack of a mediation between maternal PTSD-CB symptoms and mother-infant bonding by maternal psychological distress.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Only one other study has investigated the mechanistic relationships of maternal postpartum affective symptoms (depression/anxiety/psychological distress), PTSD-CB, and mother-infant bonding within the first year postpartum. This study found that the relationship between PTSD-CB symptoms and mother-infant bonding was mediated by depressive symptoms ( 26 ). This is in contrast to our findings of a lack of a mediation between maternal PTSD-CB symptoms and mother-infant bonding by maternal psychological distress.…”
Section: Discussionmentioning
confidence: 90%
“…Results seem to vary depending on the instrument used ( 20 ), how postpartum PTSD is defined ( 21 ), or whether comorbid symptoms of depression are considered ( 22 ).There is also evidence that maternal PTSD-CB symptoms may affect mother-infant interactions ( 23 ) and mother-infant bonding in infants born at risk, such as preterm infants ( 24 ) or infants with perinatal asphyxia ( 25 ). One recent cross-sectional web-based survey reported a medium indirect relationship between (what the authors call) “postnatal maternal PTSD symptoms” and the mother-infant bond that was fully mediated by depression symptoms ( 26 ). The authors argued that the impact of postnatal PTSD symptoms on maternal affect, cognition and behavior, and, in turn, on bonding might be less important than that of depression ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study on these associations specifically for PTSD following childbirth showed that PTSD symptoms had only an indirect effect on bonding via depression, but there was no direct effect (Blažević et al, 2019;Williams et al, 2016). Conversely, another study showed that depressive symptoms did not have a direct effect on bonding, while PTSD symptoms had ).…”
Section: Research On Ptsd Symptoms and The Couple's Relationship (Quamentioning
confidence: 98%
“…Co-morbidity of PP-PTSD and postpartum depression is high, as evident in up to 72% of cases of women endorsing PP-PTSD (Yildiz et al, 2017), and some may also endorse suicide ideation, as evident in 23% of cases (Dekel et al, in preparation). PP-PTSD may impair maternal bonding and indirectly have adverse affects on infant health (Williams et al, 2016). Hence, PP-PTSD is a problem deserving of attention.…”
Section: Introductionmentioning
confidence: 99%